A novel modeling approach to predict the output performance of photovoltaic modules under different environmental conditions. (October 2018) - Kareem, Mohamed Saleem Abdul; Saravanan, Manimaran
In this paper, an improved mathematical model of a single-diode photovoltaic (PV) module has been developed to predict the maximum power of the PV modules produced by different PV technologies, such as mono crystalline, multi crystalline, and thin film, under varying environmental conditions. The current–voltage characteristic equation of the PV module is used to extract the PV module's unknown parameters, such as light generated current, saturation current, ideality factor, series resistance, and shunt resistance at standard test condition (STC). In the proposed PV model, numerical methods are used to calculate the parameters of the PV module at STC, by introducing new equations to estimate the value of series resistance and shunt resistance. By introducing new equations IMPP and VMPP, the maximum power of different PV modules manufactured by various PV technologies at different environmental conditions is then found. In the proposed PV model, the percentage relative error obtained at maximum power is calculated and the experimental results are compared with the models that exist in the literature for different PV modules. The maximum power obtained by the proposed PV model is much closer to that obtained by the Sandia model and Ishaque two-diode model. Furthermore, the output performance of the developed PV model has close agreement with the experimentally obtained data and it is verified practically.